The Association of Time of Day of ChAdOx1 nCoV-19 Vaccine Administration With SARS-CoV-2 Anti-Spike IgG Antibody Levels: An Exploratory Observational Study. Issue 1 (February 2023) - Erber, Astrid C.; Wagner, Angelika; Karachaliou, Marianna; Jeleff, Maren; Kalafatis, Polyxeni; Kogevinas, Manolis; Pepłońska, Beata; Santonja, Isabel; Schernhammer, Eva; Stockinger, Hannes; Straif, Kurt; Wiedermann, Ursula; et al.
Data from human and animal studies are highly suggestive of an influence of time of day of vaccine administration on host immune responses. In this population-based study, we aimed to investigate the effect of time of day of administration of a COVID-19 vector vaccine, ChAdOx1 nCoV-19 (AstraZeneca), on SARS-CoV-2 anti-spike S1 immunoglobulin (IgG) levels. Participants were 803 university employees who received their first vaccine dose in March 2021, had serology data at baseline and at 3 weeks, and were seronegative at baseline. Antibody levels were determined in binding antibody units (BAU/mL) using enzyme-linked immunosorbent assay (ELISA). Generalized additive models (GAM) and linear regression were used to evaluate the association of time of day of vaccination continuously and in hourly bins with antibody levels at 3 weeks. Participants had a mean age of 42 years (SD: 12; range: 21-74) and 60% were female. Time of day of vaccination was associated non-linearly ("reverse J-shape") with antibody levels. Morning vaccination was associated with the highest (9:00-10:00 h: mean 292.1 BAU/mL; SD: 262.1), early afternoon vaccination with the lowest (12:00-13:00 h: mean 217.3 BAU/mL; SD: 153.6), and late afternoon vaccination with intermediate (14:00-15:00 h: mean 280.7 BAU/mL; SD: 262.4) antibody levels. Antibody levels induced by 12:00-13:00 h vaccination (but not other time intervals) were significantly lower compared to 9:00-10:00 h vaccination after adjusting for potential confounders (beta coefficient = −75.8, 95% confidence interval [CI] = −131.3, −20.4). Our findings show that time of day of vaccination against SARS-CoV-2 has an impact on the magnitude of IgG antibody levels at 3 weeks. Whether this difference persists after booster vaccine doses and whether it influences the level of protection against COVID-19 needs further evaluation.